Reflections on the Impact of Generative AI in Educational Assessment - Singh, Vidya; Singh, Balram (Universitas Pendidikan Ganesha, 2025)
This study is based on the characteristics of the artificial intelligence era and the current status of school education development. This paper presents the latest developments in generative artificial intelligence (GenAI) technology, along with an analysis of its definition, specifications, and key characteristics. Furthermore, it explores the application of GenAI in language understanding, text production, and other fields. By promoting the improvement of intelligent educational environments, transforming educational relationships, creatively distributing educational resources, and reshaping intelligent teaching techniques, this study also emphasizes how the widespread adoption of generative artificial intelligence in education will contribute to the reshaping of educational paradigms and human learning. The primary goal of education reform in the intelligent era is to provide guidance for successful implementation and promote steady improvement in classroom teaching within the context of AI. This study utilizes a variety of research tools to efficiently collect and analyze data. Initially, for data collection, we developed a comprehensive questionnaire survey covering a wide range of topics, including understanding, real-world applications, efficacy assessment, and current challenges related to GenAI technology. The results demonstrate trends from the data by utilizing robust data processing and statistical analysis software capabilities, which can perform descriptive and inferential statistical analyses on the questionnaire data. In addition to ensuring data security and accurate information, GenAI technology can also improve access and equality while increasing the effectiveness of teaching and learning processes.